2020
DOI: 10.1016/j.omtm.2020.09.006
|View full text |Cite
|
Sign up to set email alerts
|

WAS Promoter-Driven Lentiviral Vectors Mimic Closely the Lopsided WASP Expression during Megakaryocytic Differentiation

Abstract: Transplant of gene-modified autologous hematopoietic progenitors cells has emerged as a new therapeutic approach for Wiskott-Aldrich syndrome (WAS), a primary immunodeficiency with microthrombocytopenia and abnormal lymphoid and myeloid functions. Despite the clinical benefits obtained in ongoing clinical trials, platelet restoration is suboptimal. The incomplete restoration of platelets in these patients can be explained either by a low number of corrected cells or by insufficient or inadequate WASP expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…We therefore focus on the WAS gene promoter because WASP is only expressed in hematopoietic cells, is involved in the formation of the immunological synapse, and acts as an adaptor of TCR signals. 17,18 We have previously developed different WAS-gene-based promoters and identified the AW promoter, harboring fragments from the alternative and proximal promoter, as the best option to express transgenes in hematopoietic cells, [19][20][21] which makes it an attractive candidate for T cells expression. Here, we showed that, indeed, WAS-promoterdriven LVs (AW-LVs) partially mimicked the TCR (CD3)-expression kinetic, with a small down-regulation upon stimulation and recovered basal levels in 5-7 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore focus on the WAS gene promoter because WASP is only expressed in hematopoietic cells, is involved in the formation of the immunological synapse, and acts as an adaptor of TCR signals. 17,18 We have previously developed different WAS-gene-based promoters and identified the AW promoter, harboring fragments from the alternative and proximal promoter, as the best option to express transgenes in hematopoietic cells, [19][20][21] which makes it an attractive candidate for T cells expression. Here, we showed that, indeed, WAS-promoterdriven LVs (AW-LVs) partially mimicked the TCR (CD3)-expression kinetic, with a small down-regulation upon stimulation and recovered basal levels in 5-7 days.…”
Section: Discussionmentioning
confidence: 99%
“…Since the TRAC promoter in human mature T cells is not well characterized, we focus on a well-defined promoter that controls the expression of the WAS protein (WASP), which is involved in the formation of the immunological synapse and in translating TCR signals to several T cell functions. 17,18 We reason that WAS-promoter-driven LVs [19][20][21] could be an interesting option to express CARs due to their moderate expression levels and the functional relationship with the TCR. Here, we showed that, indeed, WAS-promoter-driven LVs partially mimicked the TCR expression kinetic both in EGFP-and CAR-expressing LVs, with a small down-regulation upon stimulation and recovering basal levels (prior stimulation) in 5-7 days.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore focus on the WAS gene promoter because WASP protein is only expressed in hematopoietic cells, is involved in the formation of the immunological synapse and acts as an adaptor of TCR signals 14,15 . We have previously developed different WAS -gene based promoters and identified the AW promoter, harbouring fragments from the alternative and proximal promoter, as the best option to express transgenes in hematopoietic cells 8,11,16 . Here we showed that, indeed, WAS -promoter driven LVs (AW-LVs) partially mimicked the TCR expression kinetic, with a small downregulation upon stimulation and recovering basal levels in 5-7 days.…”
Section: Discussionmentioning
confidence: 99%
“…Since the TRAC promoter in human mature T cells is not well defined, we focus in a well-defined promoter that controls the expression of the WASP protein, which is involved in the formation of the immunological synapse and in translating TCR signals to several T cells functions 14,15 . We reason that WAS- promoter driven LVs 8 11 16 could be an interesting option to express CARs due to their moderate expression levels and the functional relationship with the TCR. Here we showed that, indeed, WAS -promoter driven LVs partially mimicked the TCR expression kinetic both in eGFP- and CAR-expressing LVs, with a small down-regulation upon stimulation and recovering basal levels in 5-7 days.…”
Section: Introductionmentioning
confidence: 99%
“…However, a careful evaluation of the risk–benefit ratio must always be made [ 33 ]. Moreover, lentivirus-based gene therapy is already a proven therapy in WAS when there is not an optimal donor available for HSCT, although restoration of the platelet count may remain incomplete [ 43 , 44 ]. In the future, a risk profiling should be made case-by-case to identify candidates for gene therapy procedures, although currently this approach is not available for most forms of ITs, other than WAS [ 11 , 45 ].…”
Section: Pathogenesis Diagnosis and General Management Of Itmentioning
confidence: 99%